Extraction and Characterization of Inulin-Type Fructans from Artichoke Wastes and Their Effect on the Growth of Intestinal Bacteria Associated with Health. (25th September 2019) - Zeaiter, Zahraa; Regonesi, Maria Elena; Cavini, Sofia; Labra, Massimo; Sello, Guido; Di Gennaro, Patrizia
Abstract : Globe artichoke is an intriguing source of indigestible sugar polymers such as inulin-type fructans. In this study, the effect of ultrasound in combination with ethanol precipitation to enhance the extraction of long chain fructans from artichoke wastes has been evaluated. The inulin-type fructans content both from bracts and stems was measured using an enzymatic fructanase-based assay, while its average degree of polymerization (DP) was determined by HPLC-RID analysis. Results show that this method provides artichoke extracts with an inulin-type fructans content of 70% with an average DP between 32 and 42 both in bracts and in stems. The prebiotic effect of long chain inulins from artichoke extract wastes was demonstrated by its ability to support the growth of five Lactobacillus and four Bifidobacterium species, previously characterized as probiotics. Besides, we considered the possibility to industrialize the process developing a simpler method for the production of inulin-type fructans from the artichoke wastes so that the artichoke inulin preparation could be suitable for its use in synbiotic formulations in combination with different probiotics for further studies including in vivo trials.